1999
DOI: 10.1161/01.cir.100.suppl_2.ii-340
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Preconditioning by Isoflurane in Coronary Artery Bypass Graft Surgery

Abstract: Background-Experimentally, isoflurane, a commonly used volatile anesthetic agent, mimics the cardioprotective effects of ischemic preconditioning via a mechanism that could involve the activation of protein kinase C. The present study was designed to assess the clinical relevance of this observation in patients undergoing elective CABG. Methods and Results-Twenty patients were included in the study. In 10 of them, preconditioning was elicited after the onset of cardiopulmonary bypass via a 5-minute exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
106
0
9

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(116 citation statements)
references
References 34 publications
1
106
0
9
Order By: Relevance
“…Before aortic cross-clamping in patients undergoing coronary artery bypass surgery, pretreatment with isoflurane improves cardiopulmonary bypass outcome Journal of Zhejiang University SCIENCE B ISSN 1673-1581 (Print); ISSN 1862-1783 (Online) www.zju.edu.cn/jzus; www.springerlink.com E-mail: jzus@zju.edu.cn (Haroun-Bizri et al, 2001). In addition, preconditioning isoflurane may offer some additional cardioprotection in coronary artery bypass graft surgery (Belhomme et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Before aortic cross-clamping in patients undergoing coronary artery bypass surgery, pretreatment with isoflurane improves cardiopulmonary bypass outcome Journal of Zhejiang University SCIENCE B ISSN 1673-1581 (Print); ISSN 1862-1783 (Online) www.zju.edu.cn/jzus; www.springerlink.com E-mail: jzus@zju.edu.cn (Haroun-Bizri et al, 2001). In addition, preconditioning isoflurane may offer some additional cardioprotection in coronary artery bypass graft surgery (Belhomme et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…[13]. В исследуемой группе (10 пациентов) 2,5 МАК изо флурана в течение 5 минут подавались в оксигенатор с последующим 10 минутным перерывом перед пережатием аорты.…”
Section: влияние выбора метода анестезии на исход оперативного леченияunclassified
“…[2] Although clinical studies have demonstrated the translocation of the protein kinase C-d and € isoform in the human myocardium in response to sevoflurane, [3] conflicting results were found for perioperative ST segment changes, arrhythmias, troponin I (TnI), and creatine kinase-MB isoenzyme (CK-MB) release. [4,5] Morphine, an opioid, also has preconditioning effects which have been proven by many studies. [6,7] Its protective effect is exercised by way of d receptor intermediation, and some studies have shown that pure d opioid agonists may also behave in this way.…”
mentioning
confidence: 99%
“…[14] Although there are a lot of studies which use fentanyl and volatile anesthetics in balanced anesthesia protocols, fentanyl doses were given in equivalent doses to groups; therefore, only the effects of volatile anesthetics were evaluated. [3,4,15] This study aimed to compare the cardioprotective effects of anesthesia groups using a combination of low-dose fentanyl, sevoflurane, and isoflurane with a fentanyl-midazolam anesthesia group by means of clinical, biochemical, and hemodynamic parameters.…”
mentioning
confidence: 99%